Bibliometric Analysis of Islamic Economics and Finance Journals in Indonesia - Egi Arvian Firmansyah; Yudi Ahmad Faisal (Department of Islamic Economics, IPB University, 2019)
For researchers in Islamic economics and finance, publishing a journal article is one of the prerequisites to enhance the discipline of Islamic economics and finance. However, to fill out the gap in current research in the field, a researcher has to review various peer-reviewed journals. This paper utilizes a bibliometric analysis through VOSviewer software to help a researcher visualizing the performance of the Islamic economics and finance journals and the researchers in the field as well as their topic of interest. This method enables a researcher with a self-developed approach in the data collection. The result of this study shows top-five Islamic economics and finance Indonesian journals, along with the ten most productive researchers. We believe there should be an improvement in the journal management and collaboration among researchers in Indonesia for the betterment of the journals in Islamic finance in the years to come.